Increased Prevalence of Neurocognitive Impairment in Aging People Living With Human Immunodeficiency Virus: The ANRS EP58 HAND 55–70 Study. (25th July 2019) - Makinson, Alain; Dubois, Jonathan; Eymard-Duvernay, Sabrina; Leclercq, Pascale; Zaegel-Faucher, Olivia; Bernard, Louis; Vassallo, Matteo; Barbuat, Claudine; Gény, Christian; Thouvenot, Eric; Costagliola, Dominique; Ozguler, Anna; et al.
Abstract: Background: There are limited data on the comparative prevalence of neurocognitive impairment (NCI) in aging people living with human immunodeficiency virus (PLHIV) and people not living with HIV. Methods: This was a cross-sectional study of PLHIV randomly matched by age (±4 years), gender, and education with 5 HIV-uninfected individuals from the CONSTANCES cohort. PLHIV were fluent in French and sequentially included during routine outpatient visits if aged 55–70 years, with HIV viral load <50 copies/mL, and lymphocyte T-CD4 level ≥200 cells/µL in the past 24 and 12 months, respectively. The primary outcome was NCI as defined by the Frascati criteria. Multivariate normative comparison (MNC) and −1.5 standard deviations in ≥2 neurocognitive domains were secondary outcomes of NCI. Results: Two hundred PLHIV were matched with 1000 controls. Median age was 62 years, and 85% were men. In PLHIV, the median T-CD4 lymphocyte level was 650 cells/µL, and median nadir T-CD4 lymphocyte level was 176 cells/µL. NCI was found in 71 (35.5%) PLHIV and in 242 (24.2%) controls (odds ratio [OR], 1.74; 95% confidence interval [CI], 1.25, 2.41). After adjusting for confounders, HIV remained significantly associated with NCI (OR, 1.50; 95% CI, 1.04, 2.16). Adjusted results were similar with NCI defined by MNC (ORMNC, 2.95; 95% CI, 1.13, 3.50) or −1.5 SD (OR−1.5, 2.24; 95% CI, 1.39, 3.62). Conclusions: In this matched study of aging individuals, HIV was significantly associated with an increased risk of NCI after adjusting for major confounders. Results were confirmed with more stringent NCI classifications. Clinical Trials Registration: NCT02592174. Abstract : In a cross-sectional matched controlled study in people living with human immunodeficiency virus aged 55 to 70 years with controlled viremia, we found that neurocognitive impairment was significantly increased, and HIV significantly associated with impairment after controlling for other predictors.